Alignment of nautical studies at STIP Jakarta with IMO-STCW standards: a graduate perspective - Purba, Damoyanto; Wulandari, Retno Sawitri; Simanjuntak, Marudut Bernadtua (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research contributes to the existing literature by providing empirical insights into English literacy proficiency among maritime graduates in Indonesia, particularly from STIP Jakarta. By focusing on the perspectives of graduates, the study offers a nuanced understanding of the challenges and opportunities in English language education within the maritime context. The findings have implications for curriculum development, teaching methodologies, and policy-making in maritime education and training. The study concludes with recommendations for enhancing English literacy education at STIP Jakarta and other maritime institutions, including the integration of language skills into technical courses, the use of authentic materials, and the provision of language support services for students. Overall, this research highlights the importance of English literacy in preparing maritime professionals for global communication and collaboration in the maritime industry.